2021
DOI: 10.1371/journal.pone.0252427
|View full text |Cite
|
Sign up to set email alerts
|

Smokers’ cognitive and behavioural reactions during the early phase of the COVID-19 pandemic: Findings from the 2020 ITC Four Country Smoking and Vaping Survey

Abstract: Introduction COVID-19 is primarily a respiratory illness, and smoking adversely impacts the respiratory and immune systems; this confluence may therefore incentivize smokers to quit. The present study, conducted in four high-income countries during the first global wave of COVID-19, examined the association between COVID-19 and: (1) thoughts about quitting smoking; (2) changes in smoking (quit attempt, reduced or increased smoking, or no change); and (3) factors related to a positive change (making a quit atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“… 3 A multinational cross‐sectional study revealed that people who believe that COVID‐19 has more severe progress for smokers have a positive behavioral smoking change during the pandemic. 20 Our study also presents that people who believe that smoking worsens COVID‐19 progress tend to be nonsmokers or have positive behavioral changes about smoking after being diagnosed with COVID‐19.…”
Section: Discussionmentioning
confidence: 64%
“… 3 A multinational cross‐sectional study revealed that people who believe that COVID‐19 has more severe progress for smokers have a positive behavioral smoking change during the pandemic. 20 Our study also presents that people who believe that smoking worsens COVID‐19 progress tend to be nonsmokers or have positive behavioral changes about smoking after being diagnosed with COVID‐19.…”
Section: Discussionmentioning
confidence: 64%
“…Finally, several studies report growing awareness and fear of the increased risks of COVID-19 among smokers 26,27 . Beginning in March 2020, local media repeatedly highlighted the correlation between smoking and more severe COVID-19 infections, though as noted above there was some contradictory coverage early in the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…This increases the binding of human cells to the SARS-COV-2 S protein, making smokers more susceptible to infection ( Figures 1F, G ). Moreover, smoking can impair the body’s immune system, increasing the severity and mortality of COVID-19 patients ( Gravely et al., 2021 ).…”
Section: Pathological Changes and The Role Of Ace2 In Infectionmentioning
confidence: 99%